2016
DOI: 10.1056/nejmoa1602074
|View full text |Cite
|
Sign up to set email alerts
|

Cord-Blood Transplantation in Patients with Minimal Residual Disease

Abstract: BACKGROUND The majority of patients in need of a hematopoietic-cell transplant do not have a matched related donor. Data are needed to inform the choice among various alternative donor-cell sources. METHODS In this retrospective analysis, we compared outcomes in 582 consecutive patients with acute leukemia or the myelodysplastic syndrome who received a first myeloablative hematopoietic-cell transplant from an unrelated cord-blood donor (140 patients), an HLA-matched unrelated donor (344), or an HLA-mismatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
281
6
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(314 citation statements)
references
References 26 publications
15
281
6
4
Order By: Relevance
“…They clarify the role of matching in times when HSCT should provide for each patient a better outcome regarding overall survival, quality of life and costs; 19 they add caution to current concepts to 'find a donor option for every patient. [12][13][14][15][16][17] They fit with recent studies that well-matched unrelated donor HSCT showed results similar to those with matched sibling donors. They suggest complete HLA-typing (12 out of 12 antigens) of unrelated donors 26,27 before decision-making.…”
Section: Alloreactivity In Hsct a Gratwohl Et Alsupporting
confidence: 82%
See 2 more Smart Citations
“…They clarify the role of matching in times when HSCT should provide for each patient a better outcome regarding overall survival, quality of life and costs; 19 they add caution to current concepts to 'find a donor option for every patient. [12][13][14][15][16][17] They fit with recent studies that well-matched unrelated donor HSCT showed results similar to those with matched sibling donors. They suggest complete HLA-typing (12 out of 12 antigens) of unrelated donors 26,27 before decision-making.…”
Section: Alloreactivity In Hsct a Gratwohl Et Alsupporting
confidence: 82%
“…Some early promising results have triggered a rapid expansion in the use of haploidentical donors; still, they await confirmation. [12][13][14][15][16] Recent results from a large EBMT study with high-risk AML patients indicate a similar outcome at 2 years after haploidentical as compared to 10/10 antigen matched unrelated donor transplants. Non-relapse mortality was reported to be higher, relapse incidence to be lower after haploidentical HSCT, 28 follow-up was short and risk profiles of the patients different.…”
Section: Alloreactivity In Hsct a Gratwohl Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CB has a powerful GVL effect which is crucial in eliminating the drug‐resistant malignant cells. Milano et al 37. reported that among patients with pretransplantation minimal residual disease, OS after CBT was as favorable as HCT with HLA‐matched unrelated donor and much higher than HCT with HLA‐mismatched unrelated donor, and the probability of relapse was lower in the cord‐blood group than in either of the other groups, which indicated that cord blood may have a stronger GVL effect than other graft sources.…”
Section: Discussionmentioning
confidence: 99%
“…Соглас-но, преимущественно ретроспективным данным, показатели выживаемости (без лейкоза и ОВ) при использовании различных альтернативных доноров сходные, однако они более низкие после использова-ния пуповинной крови, чем после ТГСК от совмести-мых доноров (родственных и неродственных) [100]. Среди пациентов с острыми лейкозами и МДС (Fred Hutchinson Cancer Research Center), имевших мини-мальную остаточную болезнь перед трансплантацией, вероятность ОВ после трансплантации неродствен-ной пуповинной крови (4-6/6, n = 140) была, как минимум, так же благоприятна, как после трансплан-тации от HLA-идентичного неродственного донора (10/10, n = 344) и значительно выше, чем вероятность после трансплантации HLA-частично совместимого неродственного донора (9/10, n = 98), а вероятность рецидива была ниже в группе трансплантированных с использованием пуповинной крови, чем в любой из двух других групп [101].…”
Section: гаплоидентичная трансплантация и профилактика реакции «трансunclassified